PENGARUH STRES KERJA, KOMPETENSI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. JAYA MANDIRI BANGUNAN MEDAN - Kevin Andrew; Hendra Nazmi; Randy Tiatanto; Winda Yani (Universitas Methodist Indonesia, 2020)
The purpose of this study was to examine and analyze the effect of job stress, work competence, and work discipline on employee performance. The population in this study was 139 employees and the sample was 94 employees. We conducted survey research to collect data from the respondents. We used primary and secondary data and analyzed them by using multiple linear regression. The results showed that partially job stress, job competence, and work discipline had a positive and significant effect on employee performance at PT. Jaya Mandiri Bangunan Medan. Simultaneously job stress, work competence, and work discipline have a positive and significant effect on employee performance at PT. Jaya Mandiri Bangunan Medan.